Riparian zone hydrology and soil water total organic carbon (TOC): implications for spatial variability and upscaling of lateral riparian TOC exports - T. Grabs; K. Bishop; H. Laudon; S. W. Lyon; J. Seibert (Biogeosciences, 2012)
Groundwater flowing from hillslopes through riparian (near-stream) soils often undergoes chemical transformations that can substantially influence stream water chemistry. We used landscape analysis to predict total organic carbon (TOC) concentration profiles and groundwater levels measured in the riparian zone (RZ) of a 67 km2 catchment in Sweden. TOC exported laterally from 13 riparian soil profiles was then estimated based on the riparian flow–concentration integration model (RIM). Much of the observed spatial variability of riparian TOC concentrations in this system could be predicted from groundwater levels and the topographic wetness index (TWI). Organic riparian peat soils in forested areas emerged as hotspots exporting large amounts of TOC. These TOC fluxes were subject to considerable temporal variations caused by a combination of variable flow conditions and changing soil water TOC concentrations. Mineral riparian gley soils, on the other hand, were related to rather small TOC export rates and were characterized by relatively time-invariant TOC concentration profiles. Organic and mineral soils in RZs constitute a heterogeneous landscape mosaic that potentially controls much of the spatial variability of stream water TOC. We developed an empirical regression model based on the TWI to move beyond the plot scale and to predict spatially variable riparian TOC concentration profiles for RZs underlain by glacial till.